PENGARUH LATIHAN PUSH UP DAN LATIHAN BENCH PRESS TERHADAP KECEPATAN PUKULAN PADA PENCAKSILAT - Syarif Hidayat; Suprianto Kadir; Edy Dharma Putra Duhe (UNIVERSITAS NEGERI MAKASSAR, 2019)
This research is a field experimental study that aims to find out the different effects of push up and bench press exercises on punch speed on pencaksilat. The population was all students of the FOK UNG Sport Coaching Education Study Program and the sample involved were 60 people. But in accordance with the research design, two research groups were formed consisting of group A for push up exercises and group B for bench press exercises. Data analysis techniques used t-test at a significant level of 95%. Based on the results of data analysis, it can be concluded that: There is a significant effect of push up exercises on the speed of the punch on pencaksilat (to = 9,151> tt = 2,045). There is a significant effect of bench press training on punch speed on pencaksilat (to = 7,620> tt = 2,045). There is a significant difference in effect between push up and bench press exercises on punch speed on pencaksilat (to = 12,828> tt = 2,000).